Investigation of the biological function of arginine methyltransferase PRMT5 in human cancers - Jin, L (2020)
PRMT5 is a major type II arginine methyltransferase and plays a crucial role in tumorigenesis. PRMT5 is overexpressed in multiple tumour cell lines, and a high level of PRMT5 was identified as an independent factor for poor clinical outcomes in patients with cancer. PRMT5 has been identified as a potential clinical target for antitumour therapy to enable the treatment of cancers efficiently and selectively. However, studies on the role of PRMT5 are limited and there is a need to understand the mechanisms underlying the biological function of PRMT5 and its therapeutic potential. In this study, we have uncovered a functional role for the PRMT5-E2F1 axis on different aspects of cancer cell biology, including cancer cell viability, apoptosis, migration, invasion, and adhesion. Additionally, we performed a genome-wide expression analysis and identified a group of E2F1 targets that modulate cell adhesion and cellular migratory pattern, resulting in metastasis and invasion, via a PRMT5- dependent mechanism. Furthermore, the expression of PRMT5 and E2F1 was correlated, with high levels of PRMT5 and E2F1 indicating poor clinical outcomes. This study is the first time to show that the PRMT5-E2F1 axis influences cancer cell growth and division, and also augments the migration and invasive properties of tumour cells. As a positive regulator of the E2F1 axis, this strengthens the case for the use of inhibitors for PRMT5 as a viable therapeutic target, and further suggests the clinical utility of drugs targeting PRMT5.